Pre-Treatment Tumor Growth Rate Predicts Clinical Outcomes of Patients With Advanced Non-Small Cell Lung Cancer Undergoing Anti-PD-1/PD-L1 Therapy - He, Li-na; Zhang, Xuanye; Li, Haifeng; Chen, Tao; Chen, Chen; Zhou, Yixin; Lin, Zuan; Du, Wei; Fang, Wenfeng; Yang, Yunpeng; Huang, Yan; Zhao, Hongyun; et al. (Frontiers in Oncology, 2021)
Tumor growth rate (TGR; percent size change per month [%/m]) is postulated as an early radio-graphic predictor of response to anti-cancer treatment to overcome limitations of RECIST. We aimed to evaluate the predictive value of pre-treatment TGR (TGR0) for outcomes of advanced non-small-cell lung cancer (aNSCLC) patients treated with anti-PD-1/PD-L1 monotherapy. We retrospectively screened all aNSCLC patients who received PD-1 axis inhibitors in Sun Yat-Sen University Cancer Center between August 2016 and June 2018. TGR0 was calculated as the percentage change in tumor size per month (%/m) derived from two computed tomography (CT) scans during a “wash-out” period before the initiation of PD-1 axis inhibition. Final follow-up date was August 28, 2019. The X-tile program was used to identify the cut-off value of TGR0 based on maximum progression-free survival (PFS) stratification. Patients were divided into two groups per the selected TGR0 cut-off. The primary outcome was the difference of PFS between the two groups. The Kaplan-Meier methods and Cox regression models were performed for survival analysis. A total of 80 eligible patients were included (54 [67.5%] male; median [range] age, 55 [30-74] years). Median (range) TGR0 was 21.1 (-33.7-246.0)%/m. The optimal cut-off value of TGR0 was 25.3%/m. Patients with high TGR0 had shorter median PFS (1.8 months; 95% CI, 1.6 - 2.1 months) than those with low TGR0 (2.7 months; 95% CI, 0.5 - 4.9 months) (P = 0.005). Multivariate Cox regression analysis revealed that higher TGR0 independently predicted inferior PFS (hazard ratio [HR] 1.88; 95% CI, 1.04-3.40; P = 0.037). Higher TGR0 was also significantly associated with less durable clinical benefit rate (34.8% vs. 8.8%, P = 0.007). High pre-treatment TGR was a reliable predictor of inferior PFS and clinical benefit in aNSCLC patients undergoing anti-PD-1/PD-L1 monotherapy. The findings highlight the role of TGR0 as an early biomarker to predict benefit from immunotherapy and could allow tailoring patient’s follow-up.